Estimation of multivariate volatility spillover effects model of Philippine producer-consumer pork, chicken, and milkfish prices, 1990-2013 - Delfin-Villanueva, Maritess (2016)
This time-series study investigated causality using Granger causation, cointegration and volatility spillover effects ("heat waves" and "meteor shower" effects) between producer and consumer prices of chicken, pork, and milkfish markets in the Philippines, and among different consumer prices using the methodology of Generalized Autoregressive Conditional Heteroscedastic (GARCH). GARCH model estimation was done using 18-year monthly data (from January 1990 to December 2007) for each commodity under study. A total of 66 monthly observations (from January 2008 to June 2013) was done in forecasting to test the formulated models.

Findings indicate that consumer prices are riskier than the producer prices or that Philippine producers face low-return and low-return and low-risk commodity markets. Both milkfish and chicken prices were supply driven. There is interdependence between the producer and consumer prices for the pork prices. Moreover, it was found that the consumer commodity price volatility affects and is affected by its producer price volatility and price volatility of other consumer commodities ("meteor shower effects"); and the commodity price (either producer or consumer volatility is affected by its past price volatility ("heat waves" effects). Based on these results, Philippine consumers react to relative meat/fish price shocks by switching to other substitutes (meat/fish). A price increase of a certain commodity could elicit a wider range of fish/meat-related price increases with the following switching of consumption patterns: consumers prefer to purchase chicken when the price of pork increases; and they tend to buy pork when the price of milkfish and chicken increases.
Keywords: Commodity prices effect - Milkfish; Commodity prices effect - Chicken; Commodity prices effect - Pork